2007
DOI: 10.1001/archneur.64.7.984
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Alterations in Patients With Parkinson Disease and Visual Hallucinations

Abstract: Background: Visual hallucinations (VHs) occur frequently in advanced stages of Parkinson disease (PD). Which brain regions are affected in PD with VH is not well understood.Objectives: To characterize the pattern of affected brain regions in PD with VH and to determine whether functional changes in PD with VH occur preferentially in visual association areas, as is suggested by the complex clinical symptomatology.Design: Positron emission tomography measurements using fluorodeoxyglucose F 18. Between-group stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 33 publications
5
92
2
Order By: Relevance
“…Visual association cortex hypometabolism as a herald of dementia is interesting in view of the prominence of visual hallucinations in more advanced PD and PDD. Prior metabolic imaging studies suggest that visual hallucinations are associated with hypometabolism of visual association cortices (24). Visual hallucinations are by far the most common form of hallucination in PD, and incidence of visual hallucinations in PD may herald progression of dementia (25).…”
Section: Discussionmentioning
confidence: 99%
“…Visual association cortex hypometabolism as a herald of dementia is interesting in view of the prominence of visual hallucinations in more advanced PD and PDD. Prior metabolic imaging studies suggest that visual hallucinations are associated with hypometabolism of visual association cortices (24). Visual hallucinations are by far the most common form of hallucination in PD, and incidence of visual hallucinations in PD may herald progression of dementia (25).…”
Section: Discussionmentioning
confidence: 99%
“…Pathological studies have reported increased Lewy bodies within visual areas of the temporal cortex in PD patients with visual hallucinations compared with nonhallucinators [56,57]. Imaging studies have also shown selective changes within these regions [58,59]. There is some evidence that dysfunction of 5HT2A receptors within the visual pathways may be associated with the development of visual hallucinations in PD patients [60].…”
Section: Psychosis In Pdmentioning
confidence: 99%
“…Visual hallucination in PD patients is an important risk factor in terms of nursing home placement, poor quality of life, and mortality 4 . Neuroimaging studies suggested that brain regions involved in higher-order visual processing, ventral or dorsal pathways, were associated with VH in PD patients [5][6][7][8][9] . Pathologic study in Lewy body (LB) disease reported a striking association between the distribution of temporal lobe LB and VH 10 .…”
mentioning
confidence: 99%